Pengaruh Kompetensi Dan Etos Kerja Terhadap Kinerja Pegawai Kantor Camat Batang Kuis - Perangin Angin, Silvia Amelia; Ramadhani, Sri (LPPM Universitas Labuhanbatu, 2022)
The purpose of this study was to determine: (1) whether there is the influence of competence on employee performance(2) the effect of work ethic on employee performance, the effect of competence and work ethic on employee performance of the Batang quiz District Head Office Serdang. This research is motivated by the competence is still low, work ethic is still not stable, resulting in low performance of employees at the District Office Batang Quiz Data used in this study is the primary data method of data collection in this study is interviews and questionnaires. Data is processed using spss for windows version 20.0. The method of data analysis using quantitative methods is by using multiple linear regression analysis.